Biomedical Applications of Calixarenes: State of the Art and Perspectives - Pan, Yu‐Chen; Hu, Xin‐Yue; Guo, Dong‐Sheng (Angewandte Chemie International Edition, 2021)
Calixarenes (CAs), representing the third generation of supramolecular hosts and one of the most widely studied macrocyclic scaffolds, offer (almost) unlimited structure and application possibilities due to their ease of modification, which allows one to establish a large molecular library as a material basis for diverse biomedical applications. Moreover, CAs and their derivatives engage in various noncovalent interactions for the facile recognition of guests including bioactive molecules and are also important building blocks for the fabrication of supramolecular architectures. In view of their molecular recognition and self‐assembly properties, CAs are extensively applied in biosensing, bioimaging, and drug/gene delivery. Additionally, some CA derivatives exhibit biological activities and can therefore be used as new therapeutic agents. Herein, we summarize the diverse biomedical applications of CAs including in vitro diagnosis (biosensing), in vivo diagnosis (bioimaging), and therapy. Calixarenes (CAs) represent the third generation of supramolecular hosts and one of the most widely studied macrocyclic scaffolds. They offer almost unlimited structural possibilities due to their ease of modification, providing a tremendous molecular library as a material basis for diverse biomedical applications.